Veps Wedding Terminology in the Etymological and Linguo-Geographical Aspects (Veps vs. Russian) - N. G. Zaitseva (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The relevance and novelty of the study is based on the material of the “Linguistic Atlas of the Vepsian Language” (St. Petersburg, 2019), an etymological and linguo-geographical analysis of terms important from the point of view of spiritual culture that characterize the group of wedding vocabulary. The terms in question (designations of a wedding, bride and groom) fit both in the cultural background and in the language processes that were reflected in the formation of the dialectal areas of the Veps language. The results of a comparative analysis indicate the impact of the Russian language on a significant group of Veps dialects, which led to the supplantation and replacement of the main terms of the wedding ceremony with Russian lexemes ( wedding, bridegroom, bride ). The study emphasizes the peculiarity of the eastern (Belozersky) dialects (the periphery of the Veps language range), which retained their own terms for the names of the analyzed concepts. It is shown that these dialects are characterized by the conservation of archaic characters, the presence of rare (in this case, sai) and etymologically darkened (oluh) lexical items, which so far have not been able to detect etymons in related languages. The authors believe that this fact, coupled with other features of dialects, may indicate traces of the substrate, the origins of which have yet to be clarified.